A framework to support the formulation of internet strategy in traditional enterprises. (2nd November 2004) - Rangone, Andrea; Balocco, Raffaello; Bassani, Paolo; Andreoni, Matteo Conforti
The belief that the internet may have a deep impact on the competitiveness of traditional enterprises (incumbents) and may cause major changes from several points of view (processes, market relations, collaboration, etc.) has created the need for an integrated and coordinated approach to e-business projects the internet strategy. The aim of this paper is therefore to propose a reference framework to support managers in traditional enterprises in the different stages of internet strategy definition. The framework is divided into logical, non-sequential, but closely inter-linked steps typical of the strategic decision-making process, i.e. external analysis, internal analysis, e-strategic intent definition and e-business project selection. The proposed framework is applied to a case study (Electric Corporation) to help the reader comprehend and appreciate the deep impact that e-business choices may have on company competitiveness.